Educating leaders for ministry : issues and responses - Klimoski, Victor J.; O'Neil, Kevin, 1955-; Schuth, Katarina (Collegeville, Minn. : Liturgical Press, 2005)
"Draws principally on a project entitled 'Theological Teaching for the Church's Ministries' (also called the 'Keystone Conferences') and names four overarching challenges in theological education: theological differences, learning differences, integration, and assessment"--Provided by publisher.
Diversity and the formation for ministry : understanding the challenge -- Diversity and the formation for ministry : principles and practices -- Seeing things whole : a reflection on integration -- Assessment and good teaching -- Building communities of wisdom -- Responding to challenges in theological education as a community of wisdom -- Processes for faculty development -- Commentary -- What technology can teach about theological pedagogy / Thomas Esselman -- Leading change : a reflection on context, principles, and virtues / Jeanne McLean -- Reflections from the wider church.
"A Michael Glazier book."
Includes bibliographical references and index.
Keywords: Theology -- Study and teaching; Christian leadership; Pastoral theology